2017
DOI: 10.1051/matecconf/201713806001
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis Quay Wall at The Amazonehaven, Port of Rotterdam

Abstract: Abstract. The stability of any structure is an important aspect in civil engineering. This aspect is the subject of the researched quay wall at the Amazonehaven, port of Rotterdam. The quay wall with a relieving platform structure had in various section, over the entire 900m length of the quay, large deformations at the toe of the combined wall. The purpose was to analyse and quantify the influence of the deformed combined wall on the stability of the quay wall, its service lifetime. To obtain a better insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…7 The relation between the minimum penetration depths for a Trapezium Distributed Surcharges (TDS) and Uniformed Distributed Surcharges (UDS) for various load cases [1] Fig. 8 The relation between the minimum penetration depths for a Trapezium Distributed Surcharges (TDS) and Uniformed Distributed Surcharges (UDS) for various load cases [1] From the comparison between the two models it can be concluded that by modelling the distribution of the surface loads as a trapezium or uniformly the difference of minimum penetrated depth of the combined wall is considerably small. Furthermore, the field bending moment increases as the surface load increases which leads to a freely imposed bending moment.…”
Section: Resultsmentioning
confidence: 99%
“…7 The relation between the minimum penetration depths for a Trapezium Distributed Surcharges (TDS) and Uniformed Distributed Surcharges (UDS) for various load cases [1] Fig. 8 The relation between the minimum penetration depths for a Trapezium Distributed Surcharges (TDS) and Uniformed Distributed Surcharges (UDS) for various load cases [1] From the comparison between the two models it can be concluded that by modelling the distribution of the surface loads as a trapezium or uniformly the difference of minimum penetrated depth of the combined wall is considerably small. Furthermore, the field bending moment increases as the surface load increases which leads to a freely imposed bending moment.…”
Section: Resultsmentioning
confidence: 99%
“…From (9) at n→∞, we derive the following linear integral equation of convolution type to find the probability that a warehouse will never get overloaded, that is 1 -R(Q):…”
Section: Development Of the Methods For Calculating The Probability Ofmentioning
confidence: 99%
“…The general problem of security of marine transportation systems and reliability of their operation is analyzed in [8]. An analysis of stress-strained state of a berth with the use of the finite element method, but without taking into consideration the random character of the influence of operational loads on a berth, was performed in [9].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Mourillon [11] analyzes the influence of the deformed combined wall on the stability of the quay structure. Apart from the deformation of the combined wall, the designed penetrated depth was not reached.…”
Section: Hamza and Hamedmentioning
confidence: 99%